Complications after artificial urinary sphincter implantation in patients with or without prior radiotherapy. (18th October 2014) - Ravier, Emmanuel; Fassi‐Fehri, Hakim; Crouzet, Sébastien; Gelet, Albert; Abid, Nadia; Martin, Xavier
<x xml:space="preserve">Abstract</x> Objective To compare complications after implantation of an artificial urinary sphincter (AUS) in patients with or without prior radiotherapy (RT). Patients and Methods Between January 2000 and December 2011, 160 patients underwent AMS 800 AUS implantation in our institution. We excluded neurological and traumatic causes, implantation on ileal conduit diversion, penoscrotal urethral cuff position and those lost to follow‐up. In all, 122 patients were included in the study, 61 with prior RT and 61 without prior RT. All patients underwent the same surgical technique by two different surgeons. All AUS were implanted with a bulbar urethral cuff position. The mean (range) follow‐up was 37.25 (1–126) months. Results In the patients without prior RT and those with prior RT, revision rates were 32.8% vs 29.5%, respectively (P = 0.59). The median time to first revision was 11.7 months. Early complications were similar in the two groups (4.9% vs 6.5%, P = 1). Erosion rates were not significantly different (4.9% vs 13.1%, P = 0.13). However, infection and explantation were more prevalent in patients with prior RT [two (3.2%) vs 10 (16.3%), P = 0.018 and three (4.9%) vs 12 (19.6%), P = 0.016, respectively]. Finally, continence rates were not significantly different [75.4% (without prior RT) vs 63.9% (with prior RT), P = 0.23]. Conclusion AUS is the 'gold standard' treatment of male urinary incontinence after re‐education failure in patients with or without prior RT. Our experience showed similar functional outcomes in both groups but a higher rate of major complications in the group with prior RT.